A groundbreaking strategy for fabricating YAG:Ce3+ transparent ceramic films via sintering of LRH nanosheets on a sapphire substrate. Issue 84 (23rd September 2020) - Zhu, Qi; Ding, Suning; Xiahou, Junqing; Li, Siyuan; Sun, Xudong; Li, Ji-Guang
Abstract : We proposed a groundbreaking strategy for fabricating YAG:Ce 3+ transparent ceramic films via sintering of LRH nanosheets on a sapphire substrate. Abstract : Here, we proposed a groundbreaking strategy for fabricating YAG:Ce 3+ transparent ceramic films via a novel interface reaction of LRH nanosheets with a sapphire substrate without a tedious process. The incorporation of Gd 3+ greatly enhanced the emission intensity of the ceramic film by ∼11.3 times. The prepared transparent ceramic film with a high transmittance of ∼97% is a promising photo-converter for WLEDs.